Effects Of Self Etchıng Adhesıve System Whıch Have Antıbacterıal Characterıstıcs On Shear Bond Strengths After Demoralızatıon - Sibel Yıldırım; Tancan Uysal; Faruk Ayhan Başçiftçi (Turkish Journal of Orthodontics, 2004)

(untitled)
Demineralization around the brackets during orthodontic treatment is still a major problem in orthodontics. It has been reported that antibacterial bonding agents that were developed in recent years act as an antibacterial agent against bacteria that was left in the cavity and bacterial invasion resulting from micro leakage. Similarly, with the prevention of bacterial growth around orthodontic brackets caries formation could be prevented. For this reason the effects of an antibacterial bonding agent on artificial demineralization around brackets were investigated by means of bond strength evaluation. The material of this study consisted of 60 freshly extracted human premolar teeth that had no cracks or fractures. Brackets were bonded to buccal surfaces of teeth using Clearfill ABF bond that consisted of MDPB and Clearfill SE Bond and Transbond Plus bonding agents that does not contain MDPB but has the same chemical composition as Clearfill ABF Bond. All the teeth were left in experimental decalcification solution for 14 days. At the end of this period, all the brackets were tested in a universal test machine. The obtained data were analyzed using ANOVA, Tukey HSD test and chi-square analysis. The results of ANOVA showed statistically significant differences (p<0,05). Mean bond strengths were found to be clinically acceptable when compared with the results of other studies. However, the results of our study showed that brackets bonded using Clearfill ABF Bond projects significantly lower bond strengths. The 3 different adhesive systems used in this study effects the failure characteristics of brackets in an important degree.